Pengetahuan tentang Diabetes Self-Management Education dalam Mengontrol Glukosa Darah Pasien Diabetes Melitus Tipe 2 - Nur Wahyuni Munir; Wa Ode Sri Asnaniar (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
Diabetes Mellitus (DM) is a multi-system chronic disease associated with abnormal insulin production, impaired insulin use, or both Diabetes Self-Management Education (DSME) is a process that facilitates knowledge, skills and abilities in the self-care of DM patients, including monitoring regular blood glucose, diet management, physical activity, medication, and visits to health facilities. The purpose of this study was to determine the effect of diabetes self-management education on the level of knowledge and control of blood glucose in patients with type 2 diabetes mellitus in the working area of the Antang Public Health Center in Makassar. This study used quantitative research with a quasi-experimental design without a control group. Samples were taken using purposive sampling in 30 type 2 DM patients. DSME was given with a duration of 30 minutes and the level of knowledge and blood glucose were re-evaluated the following week. Educational material about DM, diet regulation, physical exercise, blood glucose control, and pharmacological therapy. Respondents given a booklet about DSME. Analysis of the data used was paired sample t test. The results showed there was an influence of DSME on increasing knowledge (p-value =